M.U.S.T. handbook 2000. (Pasig City Styles and Classics Philippines, 1998)
Offers up-to-date practical information for motorists and travelers in Manila such as emergency hotlines, utility locations, latest road rules, and vehicle maintenance. It also contains Street Maps of Metro Manila and "Easy Maps" for frequently travelled destinations in the country. This edition features additional guides on keeping healthy while vacationing.
Keywords: Automobile drivers -- Philippines -- Handbooks, manuals, etc; Automobile driving -- Philippines -- Handbooks, manuals, etc; Automobile travel -- Philippines -- Guidebooks